Urgensi Tafsir Ilmi di Masa Modern: Tanggapan Zaghlul An-Najjar Pada Kritikus Tafsir Ilmi di Dalam Kitabnya Tafsir Ayat-ayat Kauniyah Fi Al-Quranil Karim - Rizki Firmansyah; Efrita Norman; Moh Romli; Yudi Permana (LPPM Institut Nasional Laa Roiba Bogor, 2023)
In the treasures of exegesis there are several known styles of interpretation, namely the fiqh style, the adab ijtima'i style, the Sufi style, the philosophical style, the Lughawi style, and the scientific style. The latter is a style that is widely considered controversial, is half-heartedly accepted among interpreters and has even been criticized by many scholars. In simple terms, the style of scientific interpretation can mean interpretation of the Koran using scientific methods or interpretation by presenting scientific facts in interpreting the Koran, scientific interpretation can also be in the form of exploring scientific phenomena in the Koran to produce new theories, or scientific interpretation as mentioned by Farmawi. is an interpretation that is present and used to support the interpretation of the Koran itself. All of these models of understanding scientific interpretation are considered to be able to degrade the verses of the Koran to become profane because they seem to be subject to limited scientific conceptions, moreover the authors of these scientific interpretations are mostly not considered religious experts so that the validity of their interpretations is doubtful. However, among the many criticisms, there is a scientist who refutes these criticisms in his scientific interpretation book, he is Prof. Zaghlul an-Najar a geologist from Egypt who also wrote scientific interpretations of Kauniyah's Verses. The method in this study is a qualitative-descriptive method which seeks to present an overview of Zaghlul's answers to the many criticisms of scientific interpretation, the approach taken is text analysis. The results of this study reveal Zaghlul an-Najjar's criticisms and answers on the rejection of scientific interpretation and states that scientific interpretation is one of many forms of interpretation. Keywords: Koran,Interpretation,Scientific Interpretation,Zaghlul Najjar,Kauniyah verse